1990
DOI: 10.1590/s0036-46651990000600007
|View full text |Cite
|
Sign up to set email alerts
|

Parasitological and serological studies on amoebiasis and other intestinal parasitic infections in the rural sector around Recife, Northeast Brazil

Abstract: Parasitological examinations were carried out during July to December, 1989, on 485 inhabitants of four villages in São Lourenço da Mata, 25 km northwest of Recife, Pernambuco, Brazil. Approximately 99.6% of the inhabitants were infected with at least one species of intestinal parasites. A high prevalence of Schistosoma mansoni (82.1%), hookworm (80.2%) Trichuris trichiura (69.9%), Ascaris lumbricoides (61.9%) and Entamoeba coli (36.7%) infections were demonstrated. Test tube cultivation revealed that the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1
3

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 11 publications
0
15
1
3
Order By: Relevance
“…In comparable settings, Hillyer et al found a prevalence of eosinophilia of 52% and Cardoso et al a prevalence of anemia in 28%. In other studies in similar settings, prevalence of intestinal parasites ranged form 26% to 99% [15,20,21]. For ectoparasitic infection, prevalences between 16% and 43% have been described [16,21].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In comparable settings, Hillyer et al found a prevalence of eosinophilia of 52% and Cardoso et al a prevalence of anemia in 28%. In other studies in similar settings, prevalence of intestinal parasites ranged form 26% to 99% [15,20,21]. For ectoparasitic infection, prevalences between 16% and 43% have been described [16,21].…”
Section: Discussionmentioning
confidence: 93%
“…However, community-derived data on the prevalence of eosinophilia, leukocytosis and anemia and their association with intestinal and skin parasitism are scanty [14][15][16]. To investigate to which extent ectoparasites contribute to eosinophilia in the context of intestinal helminthiases, we conducted a community-based study in a rural community in Alagoas State, Northeast Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of intestinal parasitic infections of these subjects has been reported previously (Goncalves et al, 1990) .…”
mentioning
confidence: 89%
“…According to parasitological examinations in Sao Lourenco da Mata, northeast Brazil (Goncalves et aL, 1990) , four out of 485 inhabitants were positive for unembryonated eggs of Toxocara canis in stools. Therefore, a sero -epidemiological study was conducted to obtain preliminary data on the prevalence of human toxocariasis in Sao Lourenco da Mata.…”
mentioning
confidence: 99%
“…Considering that a S. mansoni female adult worm lays a large number of eggs per day, and that only a small part of them passes through the feces while the majority remains in the tissue. Handerson et al 19 , for example, infecting inbred CB/J mice, found a range of 25,511-40,143 egg/liver depending on whether the animal developed moderate splenomegaly syndrome or hypersplenomegaly syndrome. In addition, in our study, macroscopic and physiologic changes due to the presence of S. mansoni eggs on the specified organs were not observed.…”
Section: Discussionmentioning
confidence: 99%